2007
DOI: 10.1080/j003v21n01_08
|View full text |Cite
|
Sign up to set email alerts
|

When Fieldwork Takes a Detour

Abstract: This study explored the experience of occupational therapists who encountered counterproductive events during their fieldwork training. Interviews were conducted to gather information regarding the participant's perception of factors that contributed to a negative fieldwork experience. The results were divided into major categories: (1) the role of the supervisor, (2) poor supervisory characteristics, (3) the fieldwork infrastructure, (4) misconceptions in the fieldwork experience, (5) student coping strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…To decrease challenges for these students, the culture around supervising fieldwork students must be examined. In a study by Lew, Cara, and Richardson (2007), interviews were conducted to explore counterproductive events experienced by occupational therapy students during fieldwork placement. The study reported that occupational therapists felt there is a specific way occupational therapy services should be rendered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To decrease challenges for these students, the culture around supervising fieldwork students must be examined. In a study by Lew, Cara, and Richardson (2007), interviews were conducted to explore counterproductive events experienced by occupational therapy students during fieldwork placement. The study reported that occupational therapists felt there is a specific way occupational therapy services should be rendered.…”
Section: Discussionmentioning
confidence: 99%
“…Education for faculty and students related to disability awareness and examples of proper accommodations can help to improve sensitivity and increase communication (Meeks & Jain, 2018). According to a study completed by Lew et al (2007), the primary factor contributing to dissatisfaction with students' fieldwork experiences was poor supervisor educational techniques and characteristics. The authors found that supervisors had little knowledge about creating accommodations for students to enhance a successful work environment and recommended that further solutions should be developed to minimize difficulties in fieldwork for students who may need accommodations (Lew et al, 2007).…”
Section: Physical Environmental Modificationsmentioning
confidence: 99%
“…Trede and Smith (2012) have found that the quality of within-placement opportunities for verbal guided reflection may depend on the student's placement supervisor. Given that negative student experiences may be related directly to a supervisory relationship of placement (Lew, Cara, & Richardson, 2007), university-based reflection allows them to be discussed and processed. Other healthcare disciplines have similarly noted the benefit of a guided, reflective, group debrief, including physiotherapy (Delany & Watkin, 2009), nursing (Platzer, Blake, & Ashford, 2002) and occupational therapy students in Australia (Mackenzie, 2002) and the United Kingdom (Nicholls & Mackenzie, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is the responsibility of supervisors to provide feedback. When there is a lack of supervisor feedback, Lew et al (2007) reveal that it is the main reason for failing the placement. Students feel lost, disorganized and inadequate guidance to succeed during clinical placement due to lack of feedback (Rathgeber 2014).…”
Section: Theme 3: Challenges Arose During Clinical Placementmentioning
confidence: 99%